A Study on Photographs in Teaching Writing Recount - Mawaddah Mawaddah; Sofyan A. Gani; Diana Fauzia Sari (Research in English and Education Journal, 2016)
This research is conducted to find out whether teaching writing recount text by using photographs improve students’ writing ability and to find out the students’ responses toward the implementation of photographs. A number of 54 students of tenth grade level are the sample of this study. The data were collected by using test (pre-test and post-test). The instrument used the collect the data in this study by means of the test in the form of written test. The result of the test was analyzed by using writing criteria proposed by Brown (2004). In addition, some statistical formula employs to analyze the data. The result of the study revealed that the students score of writing taught by using photographs is better that the students who are not taught by using photographs where the mean score of experimental class after using of photographs is 74.92. Whereas the mean score in control class that was not taught by using photographs in teaching writing is 47.42. Thus, photograph is insinuated as one of alternative media used by the teacher in teaching English particularly teaching writing in EFL class.